The Role of Tripartite LKS to Increase Work Productivity and Conductivity - Purwanto, Agus (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2025)
Tripartite Cooperation (LKS) is vital in creating harmonious industrial relations between employers, workers, and the government. The Tripartite concept refers to the involvement of three parties: the government as a regulator, employers as employers, and workers as parties carrying out the work. Through this institution, social dialogue and deliberation between the three parties are expected to accelerate problem-solving, create fairer policies, and increase productivity and work conductivity in various industrial sectors. Tripartite LKS is a forum that allows for healthy communication and negotiation and reduces the potential for conflict in the world of work. The design of this study is a Literature Review. Literature review studies are used to collect data or synthesise sources related to research topics from various sources, including journals, books, documentation, the internet and libraries. The literature study method is a series of activities related to the method of collecting library data, reading and recording, and managing writing materials. The method of searching for articles in research journal databases and searching via the internet. The database search used is Google Scholar from 2019 to 2024. For article searches, the keywords used are also included in the data collection, namely "Tripartite LKS". Based on the results of this study, it can be concluded that the Tripartite LKS plays a very important role in increasing productivity and work conductivity. The existence of this institution not only functions as a mediator in resolving disputes but also as a facilitator in creating harmonious and mutually beneficial industrial relations. Therefore, strengthening the Tripartite LKS must be a priority in employment policies, both at the national and industrial sectors, to achieve sustainable economic development. With the Tripartite LKS running well, it is hoped that productivity and work conductivity will continue to increase, thus creating a better, more prosperous, and more productive work environment for all parties involved.